A eletrooxidação de etileno glicol: estudo dos caminhos reacionais em superfícies de PtSn/C em meio ácido - Cartonilho, Eduardo Maciel (2016)
The electroxidation of ethylene glycol and its partial oxidation products was evaluated using electrocatalysts of platinium and tin, supported on highly superficial area Vulcan XC-72 carbon. The electrocatalysts were synthesized by alcohol reduction method. Pt/C, PtSn/C 10%, PtSn/C 21% and PtSn/C 25% were characterized by Cyclic Voltammetry, Chronoamperometry, X-rays Fluorescence (XRF), X-rays Diffraction (XRD) and High Performance Liquid Chromatography (HPLC). The XRF analysis revealed that the experimental compositions of the synthesized electrocatalysts were similar to the proposed theoretical values. The results obtained by X-rays diffraction confirmed the formation of a Pt-Sn alloy. The materials revealed to have face-centered-cubic (FCC) as crystalline structure and modifications of the lattice parameters due to the addition of tin in the alloy. The electrochemical results showed a catalytic effect in the ethylene glycol oxidation. The electrocatalyst with 21wt%Sn showed a maximum current density of 4,44 x 10-5 A cm-2. The high performance liquid chromatography (HPLC) allowed to conclude that Pt/C and PtSn/C catalysts promoted the same oxidation route to produce CO2, resulting in glycolaldehyde as the main subproduct, owing to the glycolic acid formation.